Maternity Womans Experience of Inpatient Midwifery Care at the Harapan Bunda Binjai Maternity Clinic in 2023 - Sopiah Sopiah; Violent Violent (MBUnivPress, 2023)
Birth/labor is strongly influenced by pregnancy. Basically, childbirth requires midwifery care for the smooth process of labor. In a pregnancy that has no interference, it is expected that the birth of a normal baby, through a normal labor process, where the baby is born at full term, expulsion with hejan power, mother and uterine bladder contractions without experiencing severe asphyxia or birth trauma. The right to obtain midwifery services or care is one important aspect for health workers in order to provide better service. This type of research is phenomenology, which is to find out the experience of birth mothers towards inpatient midwifery care. There were six participants. The data collection process was carried out through in-depth interviews by distributing demographic data questionnaires and then recording them with a handy camera recorder. Data collection was stopped when the interview results reached data saturation. The results of the study found that efforts to facilitate labor and prevent complications that arise with care carried out such as midwife care before the baby is born by conducting examinations, installing IVs, stimulating to open the birth canal and presenting companions during labor and giving directions / encouragement of labor. Care after delivery such as fundus massage, support, cleaning the mother and checking the birth canal. Newborn care care by drying the baby, cutting the umbilical cord and doing bonding attachment so that the inner bond between mother and baby is getting closer. Based on the results of the analysis, it is hoped that it will be a source of knowledge and information for midwives in providing midwifery care to mothers in labor without neglecting biopsychosocial aspects and so that the level of public health increases. The results of this study can be used as an example or basis for conducting phenomenological research related to the same research problem.